The Word and the Flesh. Alimentary pictures and political strategies in the Theatre of Edward Bond and Rodrigo Garcia (Itinera, 2019)
This paper examines points of convergence between two major contemporary dramatists: British Edward Bond and Argentine-Spanish Rodrigo García. Indeed, even if their plays are formally very different, both stem from a radical criticism of our capitalistic consumption/aggression culture, both rely on the performativity of what is presented on stage, and both grant a prominent place to food. Food, which informs Bond’s critical and theoretical thought as well as his plays, and is omnipresent in García’s stage works, turns out to be an original dramatic constituent. By this means both dramatists establish contact with the spectator, with a view to bring him to (re)define his humanity and his political positions.